2020
DOI: 10.1371/journal.pone.0229487
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial wellbeing of orphans: The case of early school leavers in socially depressed environment in Mpumalanga Province, South Africa

Abstract: Background The emergence of a large population of orphaned youth in sub-Saharan Africa is due to the natural maturity of orphaned children. Research indicates that orphaned youth face more negative psychosocial challenges than their younger counterparts do. Furthermore, these challenges are intensified for early school leavers. This paper describes how experiencing maternal death affects the psychosocial wellbeing of orphaned youth who left school before completing high school. Methods An exploratory qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…The study has observed that the death of their parents was accompanied by multiple losses, such as loss of the family home, loss of multiple family members, loss of support from relatives, loss of friendships, loss of educational opportunities and future aspirations, and loss of childhood. This observation is consistent with previous research conducted with orphans in similar households, which concluded that these losses contributed to their psychological vulnerability [24,28,41,42].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The study has observed that the death of their parents was accompanied by multiple losses, such as loss of the family home, loss of multiple family members, loss of support from relatives, loss of friendships, loss of educational opportunities and future aspirations, and loss of childhood. This observation is consistent with previous research conducted with orphans in similar households, which concluded that these losses contributed to their psychological vulnerability [24,28,41,42].…”
Section: Discussionsupporting
confidence: 92%
“…As such, they believed that if their mothers had still been alive, their precarious situations might have been better. Moreover, the participants suppressed the emotional impact of parental loss to overcome their grief [24,28,53]. Persistent yearning for a mother has been reported elsewhere as a common expression of prolonged bereavement among orphans [28,43,54].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations